2006
DOI: 10.3386/w12422
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Acquisitions and Target Firms' Performance: Evidence From Japanese Firm-Level Data

Abstract: Using Japanese firm-level data for the period from 1994-2002, this paper examines whether a firm is chosen as an acquisition target based on its productivity level, profitability and other characteristics and whether the performance of Japanese firms that were acquired by foreign firms improves after the acquisition. In our previous study for the Japanese manufacturing sector, we found that M&As by foreigners brought a larger and quicker improvement in total factor productivity (TFP) and profit rates than M&As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…A burgeoning literature in international economics has conducted causal analyses on foreign ownership and firm performance (Djankov and Hoekman, 2000;Conyon et al, 2001Conyon et al, , 2002Harris and Robinson, 2003;Bertrand and Zitouna, 2005;Girma, 2005;Benfratello and Sembenelli, 2006;Fukao et al, 2006;Girma and Görg, 2007a,b;Heymann et al, 2007;Arnold and Javorcik, 2009, just to name a few). These papers focus on ex-post performance changes in the target firm after foreign takeover.…”
Section: Empirical and Theoretical Backgroundmentioning
confidence: 98%
“…A burgeoning literature in international economics has conducted causal analyses on foreign ownership and firm performance (Djankov and Hoekman, 2000;Conyon et al, 2001Conyon et al, , 2002Harris and Robinson, 2003;Bertrand and Zitouna, 2005;Girma, 2005;Benfratello and Sembenelli, 2006;Fukao et al, 2006;Girma and Görg, 2007a,b;Heymann et al, 2007;Arnold and Javorcik, 2009, just to name a few). These papers focus on ex-post performance changes in the target firm after foreign takeover.…”
Section: Empirical and Theoretical Backgroundmentioning
confidence: 98%
“…That is there is an expectation of post-acquisition inward transfer of inputs, perhaps including technology, organizational skills and brand names, which would raise the volume and/or value of output. It might suggest that multinational acquirers look for similar performance gains from targets in transition economies to those they generate from targets in developed western economies such Japan (Fukao et al 2006) and the United States (Conyon et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…In countries as diverse as Japan (Fukao et al 2006), Italy (Piscitello and Rabbiosi 2005) and the United Kingdom (Conyon et al 2002) foreign acquisition has been found to raise firm productivity performance, consistent with the internal transfer of technological or managerial skills or brand name advantages. Work by Girma has suggested the caveat that target firms may differ in their absorptive capacity according to both industry sector (Girma and Görg 2007) and competitive circumstances (Girma et al 2006).…”
Section: Modelling Frameworkmentioning
confidence: 94%
“…However, the fact that higher returns are available to group-based friendly mergers is consistent with our Proposition 3. Similarly Fukao, Ito, Kwon, and Takizawa (2006) estimated effects of mergers on the target firms for the period 1994-2002 and found that there was no improvement in their profitability after the merger but there was some improvement in total factor productivity for mergers between firms from the same corporate group (but not for mergers between unrelated firms). This is also consistent with Proposition 3 that friendly mergers are generally preferred in Japan.…”
Section: Business Practices and Policy Implicationsmentioning
confidence: 97%